2022
DOI: 10.35940/ijeat.e3590.0611522
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pandemic COVID19 on Air and Water Quality in India: A Systematic Review

Abstract: The Pandemic COVID-19 outbreak has significantly affected all sections of life, including a substantial reduction in economic development and production, from industrial activities to tourism and automobile congestion. During this phase, the maximum human activities were restricted, but COVID-19 came out as a blessing for the environment. Globally reported that all the environmental variables have improved since the pandemic outbreak, including water and air quality and water quality while minimizing the restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 139 publications
0
1
0
Order By: Relevance
“…Dutta et al revealed improved water quality in the Ganga at Haridwar throughout the lockdown [43,44]. However, according to some reports, the water quality of rivers (Ganga, Chambal, and Svarnarekha) has deteriorated during the pandemic [44,45]. Khan et al also reported on the Gomti River's reduced water quality at various locations throughout Lucknow during the lockdown period [35].…”
Section: Discussionmentioning
confidence: 99%
“…Dutta et al revealed improved water quality in the Ganga at Haridwar throughout the lockdown [43,44]. However, according to some reports, the water quality of rivers (Ganga, Chambal, and Svarnarekha) has deteriorated during the pandemic [44,45]. Khan et al also reported on the Gomti River's reduced water quality at various locations throughout Lucknow during the lockdown period [35].…”
Section: Discussionmentioning
confidence: 99%